Determinant factors influencing measles and rubella vaccine hesitancy among parents: A literature review - Handayani, Dewi; Najmah, Najmah; Sitorus, Rico Januar (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Measles and rubella (German measles) are diseases that can be prevented by vaccination (PD3I). Both of these diseases are acute diseases caused by viruses whose complications can cause death, especially in groups of children under five who do not receive vaccinations. Vaccination coverage for children, both basic and advanced vaccinations, has decreased in the post-Covid-19 era. Vaccination at the global level shows a decline in basic vaccination coverage from 86% (2019) to 83% (2020). Purpose: To review determinant factors influencing measles, and rubella vaccine hesitancy among parents. Method: Literature review using PRISMA guidelines with database sources coming from Sciencedirect, Pubmed, and Google Scholar published in 2019-2023. The keywords used are “vaccine hesitancy” and “determinants”. Results: The factors causing hesitancy in measles-rubella vaccination in various regions are quite complex and varied. Time barriers, distance in accessing health services, the influence of religious, cultural factors, local government support, and the influence of anti-vaccination issues through various communication media are contextual factors that need to be questioned. Individual or group/community factors that influence vaccine hesitancy include knowledge, perception of the risks and benefits of vaccines, beliefs and attitudes towards vaccination. Other factors that also influence acceptance and refusal of vaccination are support from health workers, cost barriers, and vaccine availability. Conclusion: The determining factors for doubts about measles-rubella vaccination are caused by 3 factors, namely contextual, individual, group/community influences, and the influence of specific issues regarding vaccination. Keywords: Determinant Factors; Measles-Rubella; Vaccine Hesitancy. Pendahuluan: Penyakit campak (measles) dan rubella (german measles) merupakan penyakit yang dapat dicegah dengan vaksinasi (PD3I). Kedua penyakit ini merupakan penyakit akut disebabkan oleh virus yang komplikasinya dapat menyebabkan kematian, terutama pada kelompok balita yang tidak mendapat vaksinasi. Cakupan vaksinasi pada anak, baik vaksinasi dasar maupun lanjutan era post Covid-19 mengalami penurunan. Pemberian vaksin di tingkat global menunjukkan adanya penurunan cakupan vaksinasi dasar dari 86% (2019) menjadi 83% (2020). Tujuan: Untuk meninjau faktor-faktor penentu yang memengaruhi keraguan orang tua terhadap pemberian vaksin campak dan rubella pada anaknya. Metode: Literature review menggunakan panduan PRISMA dengan sumber database berasal dari Sciencedirect, Pubmed, dan Google scholar terbitan pada 2019-2023. Kata kunci yang digunakan yakni “vaccine hesitancy” dan “determinants”. Hasil: Faktor penyebab keraguan vaksinasi campak-rubella di berbagai daerah cukup kompleks dan bervariasi. Hambatan waktu, jarak dalam mengakses pelayanan kesehatan, pengaruh faktor agama, budaya, dukungan pemerintah setempat, dan pengaruh isu anti vaksin melalui berbagai media komunikasi merupakan faktor kontekstual keraguan. Faktor individu atau kelompok/masyarakat yang memengaruhi keraguan vaksin meliputi, pengetahuan, persepsi resiko-keuntungan vaksin, keyakinan, dan sikap terhadap vaksinasi. Faktor lainnya yang juga memengaruhi penerimaan dan penolakan vaksinasi adalah adanya dukungan petugas kesehatan, hambatan biaya, dan ketersediaan vaksin. Simpulan: Faktor determinan keraguan vaksinasi campak-rubella disebabkan oleh 3 faktor, yaitu kontekstual, pengaruh individu, kelompok/masyarakat, dan pengaruh isu spesifik dari vaksinasi. Kata Kunci: Faktor Determinan; Campak-Rubella; Keraguan Vaksinasi.